(untitled) (Historia, 2021)
This paper focuses on migrant labour from southern Botswana to South Africa. The main thrust of this article is its emphasis on the positive contribution of migration to the migrants and their communities. It is argued here that although migrant labour has been blamed for having negative socio-economic effects in southern Botswana, just as in other parts of the country, it also contributed, and continues to contribute positively to the wellbeing of some households and their communities at large. Through the use of case studies from different villages in the district, the article demonstrates that poor, uneducated and unskilled young men who migrated to South Africa managed to accumulate and invest in agriculture and commercial enterprises and rose up the social ladder. In this area, migrant wages were critical in forming the basis of some enterprises, several of which are still flourishing. It also argues that some migrants acquired on-the-job skills which were later utilised productively when the migrants returned to Botswana. A similar study, but one which did not emphasise the acquisition of skills was undertaken by the author in the Bukalanga region of north-eastern Botswana in 2004.